COMMUNICATION STRATEGY IMMIGRATION OFFICE CLASS I OF BORDER CONTROL CIREBON IN SOCIALIZING NON-PROCEDURAL MIGRANT WORKERS (PMI) PREVENTION - Adam Adis Mukrotal (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2019)
In the digital era these days, the role of public relations that is referring to communication has a huge influence on the development of all aspects of an organization. One example of its implementation is the Public Relations of the Immigration Office Class I of Border Control Cirebon, which has a role as an intermediary between the community and the office which aims to carry out the socialization plan as a means of disseminating information about government policies, especially in the immigration sector. This paper discusses the concept of work steps and the role of Public Relations of the Immigration Office Class I of Border Control Cirebon in socializing the prevention of Non-Procedural Indonesian Migrant Workers (PMI) and provides an explanation in the form of a study of some of the problems encountered in the socialization process. This paper used descriptive qualitative method which aims to provide an explanation regarding the role of public relations of the Immigration Office Class I of Border Control Cirebon in socializing the prevention of Indonesian Migrant Workers (PMI) and the obstacles they face. Thus, this paper produces 2 (two) main points that have answered the research problem formulation. First, the Public Relations role of the Immigration Office Class I of Border Control Cirebon in socializing the prevention of PMI Non-Procedural has fulfilled 7 (seven) indicators of success in the public relations communication process. Second, several major obstacles have been found that hindered the socialization process, which then urgently need to be addressed immediately by the Public Relations of the Immigration Office Class I of Border Control Cirebon.